‘Physical well‐being is our top priority’: Healthcare professionals' challenges in supporting psychosocial well‐being in stroke services - Felicity A. S. Bright; Claire Ibell‐Roberts; Katie Featherstone; Nada Signal; Bobbie‐Jo Wilson; Aileen Collier; Vivian Fu (Health Expectations, 2024)
Abstract Background Following stroke, a sense of well‐being is critical for quality of life. However, people living with stroke, and health professionals, suggest that well‐being is not sufficiently addressed within stroke services, contributing to persistent unmet needs. Knowing that systems and structures shape clinical practice, this study sought to understand how health professionals address well‐being, and to examine how the practice context influences care practice. Methods Underpinned by Interpretive Description methodology, we interviewed 28 health professionals across multiple disciplines working in stroke services (acute and rehabilitation) throughout New Zealand. Data were analysed using applied tension analysis. Results Health professionals are managing multiple lines of work in stroke care: biomedical work of investigation, intervention and prevention; clinical work of assessment, monitoring and treatment; and moving people through service. While participants reported working to support well‐being, this could be deprioritised amidst the time‐oriented pressures of the other lines of work that were privileged within services, rendering it unsupported and invisible. Conclusion Stroke care is shaped by biomedical and organisational imperatives that privilege physical recovery and patient throughput. Health professionals are not provided with the knowledge, skills, time or culture of care that enable them to privilege well‐being within their work. This has implications for the well‐being of people with stroke, and the well‐being of health professionals. In making these discourses and culture visible, and tracing how these impact on clinical practice, we hope to provide insight into why well‐being work remains other to the ‘core’ work of stroke, and what needs to be considered if stroke services are to better support people's well‐being. Patient or Public Contributions People with stroke, family members and people who provide support to people with stroke, and health professionals set priorities for this research. They advised on study conduct and have provided feedback on wider findings from the research.